Robotics as an Auxiliary Tool in the Construction of Playful Didactic Resources for Children's Literature at the Emília Floriani de Oliveira Early Childhood Education Center - Dierings, Vanessa Campeol; Leoni, Edina Dors (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2024)
This work aims to present innovative pedagogical proposals that seek to contemplate literature and robotics resources for the didactic part of early childhood education as a practice that aims to develop cognitive and socio-emotional skills. Therefore, it can be stated that the use of these resources in everyday school life helps in the development of children, favoring their understanding of the world. To offer opportunities that stimulate imagination, creativity, games, make-believe, and the exploration of different materials and technological resources, the Peter Pan and Neverland Project was developed using James Matthew Barrie's work: Peter Pan as a basis. The project was applied, through didactic resources created with the support of the team of educational robotics trainers of the Municipal Department of Education of Brusque, with young children from the Emília Floriani de Oliveira Early Childhood Education Center, of the municipal network of Brusque, Santa Catarina, by activity hour teachers, guaranteeing the learning rights as determined by the National Common Curricular Base.